ANALISIS YURIDIS TERHADAP MASALAH PRAKTIK GADAI TANAH GERANG EKAN DI WILAYAH ADONARA, FLORES TIMUR - Minami, Gabriela Putri Minami; Checilia, Ananda; Henukh Ledoh, Putri Marry Louisa; Laga, Filgentius Xander; Sugiyani Boleng, Yosephin; Ngganggu, Fredenrik Charmelo; Maran , Mary Grace Megumi; Peter Lay, Benediktus (Gapenas Publisher, 2025)
This study discusses the practice of land pawning (Gerang Ekan) in the Adonara community, East Flores, and analyzes it from the perspective of national law and customary law. Land pawning is a form of traditional financial transaction that is still practiced by many indigenous peoples as an alternative to meeting economic needs, especially for those who find it difficult to access formal financing. This study uses empirical research methods with historical, legislative, and legal sociology approaches. The results of the study show that the practice of land pawning in Adonara often takes place without a clear time limit and prioritizes the principle of kinship, in contrast to the provisions of Law Number 56 of 1960 and UUPA Number 5 of 1960 which limit the period of mortgage of agricultural land to a maximum of seven years. The legal problems that arise include injustice in the distribution of revenues, uncertainty of land rights, and potential extortion. Despite this, the local community views this practice as a form of solidarity and mutual help. This study recommends the need for harmonization between national law and customary law to provide legal certainty and fair protection for all parties involved in land pawn transactions in customary territories.